ANALISIS AUDIT ENERGI LISTRIK DAN INTENSITAS KONSUMSI ENERGI PADA GEDUNG KANTOR PLN UP3 BANGKINANG - Rinaldo Mirza H Sitorus; M. Erpandi Dalimunthe; Rahmaniar (Jurnal Nasional Teknologi Komputer, 2026)
This study aims to analyze the electrical energy performance of the PLN UP3 Bangkinang Office Building through a partial energy audit and to determine the Energy Use Intensity (EUI) as an indicator of energy efficiency. The methodology includes collecting historical electricity consumption data for 2024–2025, inventorying lighting and air conditioning systems, measuring illumination levels (lux) and indoor temperature, and evaluating compliance with SNI 6196:2011, SNI 6197:2020, and Minister of Energy and Mineral Resources Regulation No. 3 of 2025. The results indicate that the EUI value of the PLN UP3 Bangkinang Office Building was 39.33 kWh/m²/year in 2024 and 40.28 kWh/m²/year in 2025, with an average of 39.81 kWh/m²/year. These values are below the benchmark of EUI < 70 kWh/m²/year, categorizing the building as highly efficient. The lighting system analysis shows that most rooms comply with the maximum lighting power density (W/m²) standard, except for the Cendana Meeting Room, which exceeds the limit. In terms of illumination level, several rooms do not meet the minimum lux standard and require optimization without significantly increasing power consumption. Meanwhile, the air conditioning system operates within a comfortable temperature range and is in good condition, contributing to stable overall energy consumption. Overall, the PLN UP3 Bangkinang Office Building demonstrates highly efficient energy performance, with opportunities for improvement in lighting distribution optimization and sustainable energy management practices to maintain a balance between energy efficiency and occupant comfort.